ANALISIS PENGARUH KUALITAS LAYANAN DAN NILAI PELANGGAN TERHADAP CITRA MEREK DALAM MENINGKATKAN MINAT MEREFERENSIKAN (Studi Kasus Pada Rawat Inap RSUD Ungaran) - Hidayati, Nurul; Soesanto, Harry; Sufian, Syuhada (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2016)
The purpose of this study was to analyze the influence of the core services quality, peripherals service quality and customers value to the brand image in increasing interest referencing. The object of this study is the inpatient service users of RSUD Ungaran. There were 101 respondents in this study and the research methods used was purposive sampling technique.Data were analyzed using structural equation model (SEM) by AMOS 23 software. SEM results indicate that the full model goodness of fit criteria is achi-square= 175.880, probability = 0.185, CMIN/DF = 1.099, GFI = 0.856, AGFI = 0.811, TLI = 0.984, and RMSEA = 0.032. The results said that the model in this study can be used.The results showed that the quality of core services have a positive and significant impact on brand image, peripherals service quality have a positive and significant impact on brand image, customers value has a positive and significant impact on brand image, brand image has a positive and significant impact on the interest referencing, core services quality have a positive and significant impact on the interest referencing, peripherals service quality have a positive and significant impact on the interest referencing and customers value have a positive and significant impact on the interest referencing.